«BEST AVAILABLE TECHNOLOGIES» IN MANAGEMENT OF SOCIO-NATURAL MANAGEMENT SYSTEMS - Marina A. Ponomareva; Natalya A. Prodanova (Advanced Engineering Research, 2012)
A set of proposals on the adaptation of foreign experience in management of the environmental impact under the Russian conditions, taking into account the regional specificity, including the creation of the regional centres on the best available technologies, the specification of their functions and interaction patterns with the federal institutions, is offered.